Effect of Drought Stress and Straw Mulch of Wheat on Morpho-Physiological Characteristics of Sesame - Jahanbakhsh Behzad Nejad; Zeinolabedin Tahmasebi Sarvestani; Ahmad Aien; Ali Mokhtassi Bidgoli (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2018)
To study the response of sesame plant under water deficit condition to the management methods, a factorial split experiment using a randomized complete block design with three replications was conducted at the Jiroft Agricultural and Natural Resources Research and Education Center in 2015. Irrigation treatments were soil field capacity, permanent wilting point, root development depth and percent availability water to sesame (with four levels: 100, 80, 60 and 40% of the required water). Ecotypes used, were Halil, Borazjan 2 and local population of Jiraft. In this experiment, wheat straw mulch used with two levels: (without using mulch and using 7.5 tons of mulch per hectare). The results showed that simple effects of drought stress and mulch and the interaction of drought stress × mulch on all measured traits were significant at the probability level of 1%. The interaction of drought stress × ecotypes × mulch was significant only for number of branches and oil percentage. The highest and lowest seed yield and oil percentage were belonged to Haleil and Borazjan 2 ecotypes, respectively. Use of 7.5 tons straw mulch per hectare resulted in improving the means of measured traits as compared to that of control. The highest percentage of oil was obtained from Halil ecotype by using straw mulch and irrigation level of 100% (53.10%), but its difference with irrigation level of 80% (52.9%) was not significant. In general, the results showed that the using of straw mulch of wheat reduced positively the effects of water deficits.